The impact on life in people with dissociative seizures or drug-resistant epilepsy - Wolfzun, Camila (2025)
The aim of this study was to analyze and compare the impact on life in people with dissociative seizures (DS) and drug-resistant epilepsy (DRE). A qualitative approach was employed using the McGill Illness Narrative Interview, which was conducted and analyzed following thematic analysis principles. Ten women diagnosed with DS or DRE participated, all from underserved sectors in Argentina. Three major themes emerged from the interviews: (1) role of emotions (emotional experiences related to the disease, both preceding the seizure and as a consequence of them). Both groups reported unpleasant emotions as a consequence of seizures, such as fear, shame, and sadness. Emotional states, including stress and anxiety, were also described as seizure triggers in both conditions. (2) Impact on social interaction (the way in which the disease impacted on social relationships). Participants with DS experienced interpersonal conflicts, mistreatment, and disbelief more frequently than those with DRE, who reported a higher perception of overprotection and hesitancy to disclose their condition. Both groups acknowledged the importance of social support from family and friends. (3) Impact on daily life activities (the way in which people discontinued activities due to the disease or continued despite it). Seizures disrupted autonomy, work, and recreational activities, though some participants continued working despite limitations. These findings provide insight into the challenges of living with DS and DRE. A deeper understanding of these experiences can inform targeted interventions to improve the quality of life for these patient populations, particularly in resource-limited settings.